2007
DOI: 10.2116/analsci.23.841
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Spectroscopic Study on Chiral Aggregation of Bilirubin-Bovine Serum Albumin Complex Formed at Liquid/Liquid Interface

Abstract: Resonance Raman spectroscopy assisted by centrifugal liquid membrane/circular dichroism (CLM-CD) and UV/Vis absorption spectroscopies was applied to measure the binding state of bilirubin (BR) in the complex with bovine serum albumin (BSA) formed at a heptane/water interface. The bisignate Cotton effects in the interfacial CD spectra and the red shift and linewidth increase of the BR absorption band around 450 nm indicated the formation of the BR-BSA complex at the interface and the chiral conversion of BR mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The latter is presumably essential for the change in CD chirality of BR bound to BSA. The conformational change of BR can only be confirmed by the CD appearance and the red shift of the 450 nm band [17]. No inversion of CD sign of the interfacial BR-BSA complex at the initial reaction stage indicates that the BSA molecule of the inter- facial BR-BSA complex is located at the aqueous phase side of the interface and less affected by the CHCl 3 dissolved in the heptane phase.…”
Section: Changes In Interfacial CD Spectra By Chloroformmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is presumably essential for the change in CD chirality of BR bound to BSA. The conformational change of BR can only be confirmed by the CD appearance and the red shift of the 450 nm band [17]. No inversion of CD sign of the interfacial BR-BSA complex at the initial reaction stage indicates that the BSA molecule of the inter- facial BR-BSA complex is located at the aqueous phase side of the interface and less affected by the CHCl 3 dissolved in the heptane phase.…”
Section: Changes In Interfacial CD Spectra By Chloroformmentioning
confidence: 99%
“…After the attainment of the absorbance maximum (4 min 40 s), the absorbance gradually decreased, as well as the fluorescence intensity, which is discussed in the next section, and CD gradually appeared (2nd and 3rd process in Scheme 1), suggesting that the aggregates of BR-BSA complex formed slowly. After undergoing a flat plateau for CD amplitude or absorbance intensity (2nd and 3rd process in Scheme 1), the completion of the complex formation and subsequent aggregation of the complex and microparticles [17] (3rd process in Scheme 1) were suggested. As comparison, the time dependences of CD and absorbance at Cv = 16.7% were shown in Fig.…”
Section: And Absorption Spectra Of Br-bsa Complex At the Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…which can be combined with other spectroscopic methods such as fluorometry [9], resonance Raman spectrometry [10][11][12][13], and circular dichroism spectropolarimetry [14,15]. Several studies on the interfacial aggregate formation of metal complexes have been carried out using CLM [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Usually, isotropic and homogeneous solution samples are employed for measuring the CD spectra; however, in some cases CD spectra of samples with unknown inhomogeneity should be measured. For example, we have observed that some chiral aggregates grown at liquid/liquid interfaces show chiral activity, [3][4][5][6][7][8] but the chirality of the individual micro-aggregate can not measured by a conventional CD spectropolarimeter. Also, almost all biological samples have inhomogeneity, because they consist of various tissues.…”
Section: Introductionmentioning
confidence: 99%